Senam Kaki Menggunakan Koran terhadap Kadar Gula Darah pada Pasien Diabetes Melitus Tipe II - Mawar Septiyani; Teti Hayati; Wilda Fauzia (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effect of newspaper foot exercises on blood sugar levels in patients with type II diabetes mellitus at the Kemayoran Community Health Center. The method used was a pre-experimental study with a one-group pre-test-post-test design. The results showed that respondents' blood sugar levels before the intervention ranged from 167 to 361 mg/dL, with an average of 232.51 mg/dL. After the newspaper foot exercises, blood sugar levels decreased to 132–287 mg/dL with an average of 189.66 mg/dL. The Wilcoxon test yielded a p-value of 0.000 (<0.05). In conclusion, newspaper foot exercises are effective in lowering blood sugar levels in patients with type II diabetes mellitus.   Keywords: Type II Diabetes Mellitus, Non-Pharmacological Intervention, Blood Sugar Levels, Foot Exercises